2004
DOI: 10.1007/s00401-004-0943-y
|View full text |Cite
|
Sign up to set email alerts
|

Exercise preconditioning ameliorates inflammatory injury in ischemic rats during reperfusion

Abstract: There is evidence that physical activity is associated with decreased brain injury resulting from transient middle cerebral artery (MCA) occlusion. We investigated whether exercise could reduce stroke-induced brain inflammatory injury and its associated mediators. Sprague Dawley rats (3 months old) were subjected to 30 min exercise on a treadmill each day for 1-3 weeks. Stroke, in exercised and non-exercised animals, was then induced by a 2-h MCA occlusion followed by 48 h of reperfusion using an intraluminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 72 publications
7
83
0
Order By: Relevance
“…In addition, regular exercise training-associated adaptation is a precondition against treatment with H 2 O 2 , which causes a significant degree of damage for untrained subjects (317). Moreover, when heart attacks or strokes are simulated in untrained and trained animals, the infarct size is significantly smaller in the trained groups (39,81), showing that regular exercise acts as a preconditioning tool (317) by enhancing the adaptive zone, by narrowing the theoretical distance between functional and biological endpoints. A great deal of evidence exists that suggests that regular exercise-induced adaptations to ROS handling, through redox signaling, including antioxidant and oxidative damage repair systems, significantly contribute to the health-promoting effects of regular exercise.…”
Section: Figmentioning
confidence: 99%
“…In addition, regular exercise training-associated adaptation is a precondition against treatment with H 2 O 2 , which causes a significant degree of damage for untrained subjects (317). Moreover, when heart attacks or strokes are simulated in untrained and trained animals, the infarct size is significantly smaller in the trained groups (39,81), showing that regular exercise acts as a preconditioning tool (317) by enhancing the adaptive zone, by narrowing the theoretical distance between functional and biological endpoints. A great deal of evidence exists that suggests that regular exercise-induced adaptations to ROS handling, through redox signaling, including antioxidant and oxidative damage repair systems, significantly contribute to the health-promoting effects of regular exercise.…”
Section: Figmentioning
confidence: 99%
“…Regular exercise has also been shown to reduce brain inflammation in response to immune challenges, such as stroke [172] or peripheral infection [173]. And, as in the periphery, exercise-induced IL-6 production in the brain can exert an anti-inflammatory and protective role by inhibiting inflammatory TNFa signalling and attenuating neural cell death [174].…”
Section: Physical Fitness Promotes An Antiinflammatory Statementioning
confidence: 99%
“…Multiple studies using human and animal models have shown that preischemic physical activity reduces stroke impact on functional motor outcomes, edema, and infarct volume. The same studies also attributed these benefits to the mechanism of decreasing inflammation, and increasing brain-derived neurotrophic factor (BDNF) expression [2][3][4][5][6]. In many cases, however, stroke patients are unable to adhere to the physical activity regimen following their ischemic episodes due to a wide range of individual factors such as stroke severity, preexisting and comorbid conditions, motivation, fatigue, and depression.…”
Section: Introductionmentioning
confidence: 99%